The Role of Nursing Intervention in Postoperative Pain Management: A Scoping Review - Navy Sealsi Adinda Prisca Marina Marina; I Made Dwi Budhiasa Ari Serengga; Dwi Puji Lestari; Kiki Fajar Nurhidayah; Yulis Setiya Dewi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Surgical or perioperative procedures are always followed by anesthesia, which is a state without pain sensation. Patients who undergo perioperative procedures experience moderate to severe postoperative pain. Therefore, postoperative pain management in addition to analgesics is needed to help stabilize pain intensity. The purpose of this study is to determine the role of nurses in the implementation of pain management programs in postoperative patients. Methods: This study used the ScR scoping reviews approach and used PRISMA-ScR for article identification and screening. The articles were obtained from several databases, include Scopus, PubMed, ScienceDirect, and ProQuest. Articles published in the last 5 years (2019-2024) and using keywords related to the role of nurses, pain management, and postoperative. The review of 12 articles was conducted systematically with a data extraction process to identify aspects of research objectives, methods, samples, results and to find gaps or new findings that can be used as recommendations. Results: From the findings of 5,175 initial articles, 12 articles were produced that met the inclusion criteria. The analysis obtained several points of the role of nurses in postoperative pain management: (1) Pain management with relaxation in the form of guided imagery, benson relaxation and a combination of aromatherapy relaxation in postoperative patients; (2) Pain management with simple physical exercise techniques on the bed and mabulation support and effective cough breathing exercises (3) Multidisciplinary and complementary collaboration for complementary therapy of pain management with acupuncture techniques, foot and hand massage; (4) Electrical stimulation therapy, namely TENS as a stimulus for pain relief. Conclusions: These findings confirm the importance of the role of nurses to ensure continuity of care in postoperative pain management and invasive measures.